An Assessment of the Protection of Children under the Nigerian Data Protection Regulation 2019 - Olubiyi, Ifeoluwa A.; Kwame-Okpu, Aghohovwia (ABUAD Law Journal, 2021)
Data protection which evolved out of the established notion of privacy to deal with threats posed to privacy by information communications technology is concerned with the use of laws and policies to regulate the collection and processing of personal data. This paper discusses the level of protection given to children under the Nigerian Data Protection Regulation which is the primary law on the subject matter in Nigeria. To achieve its aim, the paper examines the development of data protection as an offshoot of the established notion of privacy and the need to specifically protect children before discussing the level of data protection afforded children in Nigeria with a view to showing its adequacy or otherwise. The paper found that as a vulnerable group, children face privacy risks posed by information communications technology and may unknowingly disclose personal information due to several factors. So, it is necessary for data protection law to establish safeguards for their protection. The paper also found that the Nigerian Data Protection Regulation does not designate children as vulnerable groups. Further findings are that the law also does not adequately regulate the processing nor provide for the protection of personal data belonging to children and some of its inadequate provisions may adversely affect the effective protection of children’s privacy in today’s digital world. To remedy these shortcomings the paper makes some recommendations that can be implemented immediately and in the future before concluding.